Expression of e-cadherin and vimentin in lesions of oropharynx - Thankam, Dhanya R.; A., Aria Jyothi (International Journal of Advances in Medicine, 2021)
Background: Oral squamous cell carcinoma is the 6th most common malignancy in the world and ranks as first in males in Indian sub-continent. Vimentin is an intermediate filament found in mesenchymal cells and e-cadherin is an adhesion molecule found in epithelial cells. The objective of the study is to evaluate the expression of e-cadherin and vimentin in lesions of oropharynx and to assess the sensitivity, specificity and positive predictive value of e - cadherin and vimentin in oropharyngeal squamous cell carcinoma (OPSCC), against routine H and E stained histopathological diagnosis. Methods: 100 oropharyngeal biopsy specimens taken and routine H and E stained histopathological slide diagnosis made. E-cadherin and vimentin expression studied in OPSCC, moderate to severe dysplasia, mild dysplasia and benign cases and its sensitivity, specificity, positive predictive value and negative predictive value analysed using appropriate statistical tools. Results: Vimentin positivity was observed in 70 out of 79 OPSCC, 2 out of 3 cases of moderate - severe dysplasia, 0 out of 2 mild dysplasia and 2 out of 16 benign lesions. Out of 79 cases of OPSCC, 15 were e-cadherin negative, 27 showed low and 37 cases showed high membraneous positivity. Conclusions: We observed a significant decrease in e-cadherin membrane expression from dysplasia to carcinoma insitu to invasive carcinoma and a significant increase in vimentin expression with progression of the tumor. E-cadherin is a good prognostic marker whereas vimentin expression indicates a poor prognosis.